2006
DOI: 10.1038/sj.onc.1209510
|View full text |Cite
|
Sign up to set email alerts
|

The SRC family kinase LYN redirects B cell receptor signaling in human SLP65-deficient B cell lymphoma cells

Abstract: SLP65 represents a critical component in (pre-) B cell receptor signal transduction but is compromised in a subset of pre-B cell-derived acute lymphoblastic leukemia. Based on these findings, we investigated (i.) whether SLP65-deficiency also occurs in mature B cell-derived lymphoma and (ii.) whether SLP65-deficient B cell lymphoma cells use an alternative B cell receptor signaling pathway in the absence of SLP65. Indeed, expression of SLP65 protein was also missing in a fraction of B cell lymphoma cases. Whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…These results suggest that the sequence of events in the lymphoma cells might be different from those in normal B cells. In support of this speculation, Sprangers et al 35 have found several human lymphoma cell lines that carry mutations in the BLNK gene including deletions, 3 0 truncations, mutations in splice sites and small deletions in tyrosine residue codons. Moreover, BCR signaling can be transmitted by the direct interaction between Lyn and PLCg1, causing calcium mobilization in the absence of BLNK.…”
Section: Discussionmentioning
confidence: 97%
“…These results suggest that the sequence of events in the lymphoma cells might be different from those in normal B cells. In support of this speculation, Sprangers et al 35 have found several human lymphoma cell lines that carry mutations in the BLNK gene including deletions, 3 0 truncations, mutations in splice sites and small deletions in tyrosine residue codons. Moreover, BCR signaling can be transmitted by the direct interaction between Lyn and PLCg1, causing calcium mobilization in the absence of BLNK.…”
Section: Discussionmentioning
confidence: 97%
“…39 Finally, in case of SLP-65 (BLNK) linker protein deficiency, a direct oncogenic activity was also demonstrated for the Lyn kinase. 40 Despite its oncogenic and regulatory properties, PAG appears redundant in lymphocyte physiology because mice with a disrupted Cbp/PAG gene exhibit normal lymphocyte activation and maturation. 41,42 PAG may therefore constitute an adaptor selectively capable of increasing the oncogenic potential of Lyn in B-NHL cells.…”
Section: Discussionmentioning
confidence: 99%
“…37 It is well established that Lyn-SFK are important mediators of IL7 and pre-BCR stimulation, but the exact mechanism is unknown. 38 Lyn-SFKs have been linked to Stat5 activation, 39 and IL7-STAT5 signaling pathways have been shown to be critical for repressing Igl-k rearrangements at the pro-B stage, 40,41 which could account for relatively high Igl-k rearrangements observed in the Runx1-deficient pro-/pre-B cells. Furthermore, the critical role of Lyn-SFK in pre-BCR signaling has also been demonstrated in mice with either a triple knockout (Blk, Lyn, Fyn) or that are transgenic for a constitutively active form of Blk.…”
Section: Runx1mentioning
confidence: 99%